Evaluation of antibiotic prescribing pattern during hospitalisation: A preliminary clinical audit from a Malaysian teaching hospital - Elnaem, Mohamed Hassan Abdelaziz; Jamal, Muhammad Hazim; Noor Ismadi, Muhammad Nur Shafiq; Pauzi, Muhammad Faris; Mohd Shaufi, Muhammad Anis; Hassan, Muhammad Fakhrul Asyraf Kamarulzaman (Wolters Kluwer Medknow Publications , Wolters Kluwer India Pvt Ltd, 2020)
Inappropriate prescribing of antibiotics by healthcare providers is a leading contributor to antibiotics resistance and increasing hospital stay worldwide. There is a relatively few data available on how appropriately the changing of antibiotics during the same hospital stay occurs. Objectives: This study aimed to investigate and evaluate the prescribing pattern by healthcare providers during hospitalisation in a Malaysian teaching hospital. Materials and Methods: a preliminary clinical audit (N=70) was conducted over four weeks in the wards of a Malaysian teaching hospital. The evaluation was performed according to the National Antibiotic Guidelines (NAG), including adult patients more than 18 years old who were prescribed with at least two different antibiotics throughout the same hospitalisation period. Descriptive statistics were used to present the findings. Results: The most commonly prescribed as a first antibiotic was amoxicillin/clavulanate combination (25.7%) while cefuroxime was the most common second antibiotics choice contributing to 16.7% compared to other antibiotics. Besides, a considerable number of cases (30%) have their first antibiotic change after one day only. Multiple antibiotics courses were more prevalent among patients with lower respiratory tract infections compared to other diseases. Surprisingly, only about 57.1% of the prescribed antibiotics regimens complied with NAG recommendation mainly due to the inappropriate choice of prescribed antibiotic. Conclusion: There is a need to improve further the appropriateness of antibiotic prescribing by focusing on supporting the rational choice of prescribed antibiotics throughout the hospitalisation.